Chemical shift calibration of 1H MAS NMR liver tissue spectra exemplified using a study of glycine protection of galactosamine toxicity - Hong, Young-Shick (Magnetic resonance in chemistry : MRC, 2009)
High-resolution (1)H magic angle spinning (MAS) NMR spectroscopy is a useful tool for analysing intact tissues as a component of metabonomic studies. The effect of referencing MAS NMR spectra to the chemical shifts of glucose or to that or trimethylsilylpropionic acid on the resultant multivariate statistical models have been investigated. It is shown that referencing to known chemical shifts of either alpha-glucose or beta-glucose in (1)H MAS NMR-based metabolic data of intact liver tissues is preferred. This has been exemplified in studies of galactosamine toxicity in the rat where co-administration of glycine ameliorates the toxic response. This approach leads to better aligned sets of spectra and reduces the inter-sample variability in multivariate statistical models. If glucose is not present in the tissue under study, then a number of alternative internal reference chemical shifts are presented. Finally, the chemical shift difference between that of the anomeric H1 proton of alpha-glucose and residual water is confirmed as a suitable internal temperature calibration method